2016
DOI: 10.1364/oe.24.001222
|View full text |Cite
|
Sign up to set email alerts
|

Flexible calibration method for telecentric fringe projection profilometry systems

Abstract: A newly developed flexible calibration algorithm for telecentric 3D measurement systems is presented in this paper. We theoretically analyzed the similarities and differences between the telecentric and entocentric system. The telecentric system can be calibrated with the aid of the traditional 2D planar calibration method. An additional two-step refining process is proposed to improve the calibration accuracy effectively. With the calibration and refining algorithm, an affine camera can be calibrated with a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Chen et al [13] proposed raising the calibration plate for three-dimensional space calibration; however, increasing the calibration plate will introduce errors, and the operation is inconvenient [22]. Because we need to measure the height of objects in three-dimensional space, a two-dimensional calibration plate or calibration cube should be used to obtain the M matrix [23].…”
Section: ) Calibration Of the Telecentric Vision Systemmentioning
confidence: 99%
“…Chen et al [13] proposed raising the calibration plate for three-dimensional space calibration; however, increasing the calibration plate will introduce errors, and the operation is inconvenient [22]. Because we need to measure the height of objects in three-dimensional space, a two-dimensional calibration plate or calibration cube should be used to obtain the M matrix [23].…”
Section: ) Calibration Of the Telecentric Vision Systemmentioning
confidence: 99%
“…For example, the HP 3D SLS Pro [9] (the benchmark scanner in this work) and EinScan-Pro+ [10] are professional-grade commercial scanners, but can only achieve 50 µm spatial resolution. Rao et al [11] achieved 15 µm spatial resolution, and Liu et al [12] have achieved 10 µm but it is still not precise enough for EBM melt pool monitoring. Challenges exist in 3D scanner system design and calibration procedure, which motivated the research work reported in this paper.…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%
“…Fringe projection profilometry is a state-of-the-art method in order to characterize the geometry information of three-dimensional (3-D) objects, as it allows a noncontact, fast, and areal data acquisition in the micrometer range. [1][2][3] If a measurement setup with a small field-of-view (FOV) is required, telecentric lenses can be employed either in stereo vision (with 4,5 or without additional projector 6,7 ) or in single camera-projector configurations (with entocentric [8][9][10] or telecentric projector 11,12 ) or telecentric Scheimpflug approaches. 13,14 The calibration of a telecentric structured light sensor is not as straightforward as in the entocentric case, as a telecentric camera cannot be modeled by the pinhole camera but requires the introduction of the so-called affine camera model instead.…”
Section: Introductionmentioning
confidence: 99%